Analysis of Negative and Positive Impacts of Conflict between Employees at PT Tirtakencana Tatawarna Rantauprapat - Amelia Marisna; Elvina Elvina; Yudi Prayoga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study was conducted to analyze the negative and positive impacts of conflicts between employees at PT Tirtakencana Tatawarna Rantauprapat. This study aims to determine whether conflicts that occur between employees have an impact on employee performance. This study uses a descriptive qualitative approach, the samples in this study are managers, supervisors and employees as the actors under study. Data collection is done by conducting interviews, observation and documentation. Based on the results of data analysis, it can be concluded that: first, there is no negative impact from the occurrence of conflicts between employees at PT. Tirtakencana Tata Warna Rantauprapat. Second, there is a positive impact from the occurrence of conflicts between employees at PT Tirtakencana Tatawarna, one of the impacts is making employees more mature in making decisions and not rash in acting that will harm themselves and also reduce dependence between employees and employees so that they understand better character of each side.